Assessment of three food types during the preliminary growth of the "white cachama" (piaractus brachypomus) in Pastaza, Ecuador - Lam Romero, Francisco Vidal (2015)
The White Cachama, a very common species in our rivers, is an important part of the fishing potential of the area. This species has characteristics suitable for use in commercial farming programs, because of its rapid growth rate, resistance to handling and disease. This study evaluated the overall performance of the White Cachama, based on weight, height, and economic indicators. The  White Cachama were grown in floating cages using three diets: Nutritionally balanced pellets (1) Alternative Foods (2) and Nutritionally balanced pellets plus Alternative Foods Diet (3). The research was conducted in Santa Clara, a Province of Pastaza, Ecuador. The productive indicators evaluated were total weight achieved  (g)  daily weight gain  (g)  and length  (cm). Additionally, an economic assessment was performed. The balanced diet produced the best weights of the animals averaging 228.3 g and the worst alternative feeding the animals which averaged only 115.1 g. In line with the above the best daily weight gain it was obtained in Diet 1 (1.52 g) and the worst in 2 (0.76 g). The average size was 17.29 cm for diet 1 with the best performance and 12.74 cm 2 for the worst. It was concluded that the diets used in the study are a valid food sources for raising the White Cachama (P. brachypomus) in our study conditions. Diet 3 is both economically and biologically feasible. With the Balanced diet (1) the commercial weight was achieved at the optimal time, while with diet 3 optimal weight was not obtained for trade, but the fish were considered attractive for consumption.